Dry Socket following Tooth Extraction in an Iranian Dental Center: Incidence and Risk Factors Dry Socket following Tooth Extraction in an Iranian Dental Center: Incidence and Risk Factors - Majid Eshghpour; Amir Moradi; Amir Hossein Nejat (Mashhad University of Medical Sciences, 2013)
Introduction: Dry Socket (DS) is a common post-surgical complication following extraction of permanent teeth. Various risk factors has been mentioned for this complication including gender, age, amount of trauma during extraction, difficulty of extraction, inappropriate irrigation, infection, smoking, and oral contraceptive use. The aim of this study was to evaluate the incidence of DS among permanent teeth extraction in an Iranian Oral and Maxillofacial clinic and also to identify risk factors. Methods: This cross-sectional study performed at Mashhad Faculty of Dentistry between January 2009 and June 2009. Total of 785 patients who underwent non-surgical extraction of permanent teeth included in this study. A questionnaire with two sections designed to collect demographic, medical, and extraction-related data along with data regarding cases returning with DS. Data were reported descriptively and analyzed using Chi-square test with 95% confidence interval. Results: Total of 1073 teeth included in this study. 46.11% of patients were male and 53.89% were female. The mean age of participants was 32.68 ± 17.63 years. Total of 31 patients (2.89%) were diagnosed with dry socket. Smoking and oral contraceptives intake had significant association with incidence of DS. In contrast, age, gender, medical status, tooth location, number of anesthetic carpules, anesthetic technique, pre-extraction antibiotic consumption, and academic year of students had no significant association with the incidence of DS. All cases with DS treated and were followed until resolution of DS. Conclusion: it is recommended to identify high risk groups (smokers and oral contraceptive takers) when performing extraction and to perform preventive measures in these group of patients to attenuate postoperative complications.